Associations of coffee and tea consumption with lung cancer risk. Issue 10 (28th December 2020) - Zhu, Jingjing; Smith‐Warner, Stephanie A.; Yu, Danxia; Zhang, Xuehong; Blot, William J.; Xiang, Yong‐Bing; Sinha, Rashmi; Park, Yikyung; Tsugane, Shoichiro; White, Emily; Koh, Woon‐Puay; Park, Sue K.; et al.
Abstract: Associations of coffee and tea consumption with lung cancer risk have been inconsistent, and most lung cancer cases investigated were smokers. Included in this study were over 1.1 million participants from 17 prospective cohorts. Cox regression analyses were conducted to estimate hazard ratios (HRs) and 95% confidence intervals (CIs). Potential effect modifications by sex, smoking, race, cancer subtype and coffee type were assessed. After a median 8.6 years of follow‐up, 20 280 incident lung cancer cases were identified. Compared with noncoffee and nontea consumption, HRs (95% CIs) associated with exclusive coffee drinkers (≥2 cups/d) among current, former and never smokers were 1.30 (1.15‐1.47), 1.49 (1.27‐1.74) and 1.35 (1.15‐1.58), respectively. Corresponding HRs for exclusive tea drinkers (≥2 cups/d) were 1.16 (1.02‐1.32), 1.10 (0.92‐1.32) and 1.37 (1.17‐1.61). In general, the coffee and tea associations did not differ significantly by sex, race or histologic subtype. Our findings suggest that higher consumption of coffee or tea is associated with increased lung cancer risk. However, these findings should not be assumed to be causal because of the likelihood of residual confounding by smoking, including passive smoking, and change of coffee and tea consumption after study enrolment. Abstract : What's new? Up to now, the data have been unclear regarding the effects of coffee and tea on lung cancer, in part because of cigarette smoking as a confounding variable. Here, the authors investigated the effects of coffee and tea drinking on lung cancer, with particular care to include non‐smokers and non‐European populations. They evaluated data from 1.1 million individuals in 17 prospective cohorts, and their analysis suggests that higher intake of coffee or tea is associated with increased lung cancer risk. Among never smokers, the HR for coffee drinkers was 1.35 and for tea drinkers, 1.37.